Long-term results after surgical treatment of subacromial pain syndrome with or without rotator cuff tear - Inderhaug, Eivind (J Orthop, 2018)
PURPOSE: Some studies suggest a common degenerative path might contribute to a range of shoulder diseases involving subacromial pain syndrome and full-thickness rotator cuff tears. One could therefore theorize arthroscopic subacromial decompression and rotator cuff repair as interventions at different stages of a degenerative shoulder disease. Few studies have compared long-term outcomes after these two procedures. METHOD: Matched case-controls undergoing arthroscopic rotator cuff repair combined with subacromial decompression (N = 180) or subacromial decompression only (N = 180) were evaluated pre- and 7.5 years postoperatively using QuickDASH score, VAS of function, VAS of pain and VAS of satisfaction. New surgery and complications were recorded. Baseline characteristics were related to outcomes to investigate predictors of good/poor outcome. RESULTS: A general improvement from baseline was seen − from 51 to 14 (QuickDASH) in the combined group and from 53 to 16 in the decompression only group. No differences in outcomes were seen between groups (n.s.). Age above 55 at surgery predicted better VAS of function (P = .04) while acute onset of symptoms predicted better QuickDASH in the combined group (P = 0.03). None in the decompression group had undergone later rotator cuff repair. CONCLUSION: Major improvements in pain/function were seen at mid- to long-term after isolated arthroscopic subacromial decompression and combined decompression/rotator cuff repair. Several patient-specific factors predicting worse outcomes were identified.